Addressing a forgotten struggle: Victims of enforced disappearance in Africa - Alejandra Vicente; Eva Nudd (Torture)
Abstract: Enforced disappearance in Africa occurs on a daily basis and no one is immune from becoming a victim. The practice, which commenced during the colonial times, continues today. Governments routinely use enforced disappearance as a tool to oppress the opposition and instill fear among the population in order to retain power. It is also used in the context of migration, as well as in many other contexts and against a variety of victims. As enforced disappearance is a crime committed by State officials with an interest in concealing it, the statistics on its prevalence are limited and do not show the full extent of the crime in Africa. Further, the lack of political will to acknowledge the use of this practice means that many African States lack policies and laws to prevent, investigate and punish the perpetrators of enforced disappearance. In the last two years, the African Commission on Human and Peoples’ Rights adopted two resolutions raising awareness of the crime and paving the way for drafting and adopting specific guidelines to address this crime, which would be a first step in setting up a holistic framework to eradicate enforced disappearances on the continent.